Fourth IEEE International Conference on Data Mining (ICDM'04)
DOI: 10.1109/icdm.2004.10043
|View full text |Cite
|
Sign up to set email alerts
|

Finding Constrained Frequent Episodes Using Minimal Occurrences

Abstract: Recurrent combinations of events within an event sequence, known as episodes, often reveal useful information.Most of the proposed episode mining algorithms adopt an apriori-like approach that generates candidates and then calculates their support levels. Obviously, such an approach is computationally expensive. Moreover, those algorithms are capable of handling only a limited range of constraints. In this paper, we introduce two mining algorithms -Episode Prefix Tree (EPT) and Position Pairs Set (PPS) -based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Many studies have been done on extracting concise representations of episodes to reduce the number of discovered episodes and have shown that those representations can provide better accuracy for various prediction tasks (Amiri et al, 2019;Ao et al, 2019;Li et al, 2018;Liao et al, 2016Liao et al, , 2018Ma et al, 2004;Méger & Rigotti, 2004;Tatti & Cule, 2011Zhou et al, 2010;Zhu et al, 2012Zhu et al, , 2011.…”
Section: Episodes With Concise Representationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have been done on extracting concise representations of episodes to reduce the number of discovered episodes and have shown that those representations can provide better accuracy for various prediction tasks (Amiri et al, 2019;Ao et al, 2019;Li et al, 2018;Liao et al, 2016Liao et al, , 2018Ma et al, 2004;Méger & Rigotti, 2004;Tatti & Cule, 2011Zhou et al, 2010;Zhu et al, 2012Zhu et al, , 2011.…”
Section: Episodes With Concise Representationsmentioning
confidence: 99%
“…Maximal episodes (ME; Ao et al, 2019;Fournier-Viger et al, 2022;Ma et al, 2004) An interesting property of maximal episodes is that ME ⊆ CE ⊆ FE. Thus, maximal episodes are a more compact representation than the closed episodes.…”
Section: Maximal Episodesmentioning
confidence: 99%
See 3 more Smart Citations